General equilibrium properties of the term structure of interest rates - Benninga, Simon; Protopapadakis, Aris (Journal of Financial Economics, 1986)
The paper examines the allocation of consumption and investment in a three-date binomial model in order to determine the sign of the real term structure premium in general equilibrium. When production functions are concave, markets are complete, and future production possibilities are the same irrespective of which state of the world occurs, the term structure premium will be positive. In incomplete markets, constant or increasing absolute risk aversion is sufficient to guarantee a positive term structure premium, although in the (more likely) case of decreasing absolute risk aversion a negative premium cannot be ruled out.